Influence of low-frequency electromagnetic fields against the germination of wheat (Triticum aestivum L.) seeds (Romanian Biotechnological Letters, 2025)
The biological effects produced by low-frequency of the electromagnetic fields on the seed germination of the wheat were studied on Triticum aestivum L. Electromagnetic fields with frequencies between 10 and 200 Hz and an increasing of the intensity up to 5 Hz have been used. The density value applied to the electromagnetic fields was 2mT. Wheat (Triticum aestivum) seeds were used as biological material. The biological response was established by determining seed germination and it was performed by measuring the length of the germinated seed seedlings hypocotyls. The peroxidase level has been used as biological marker for both seedling hypocotyls and rootlets. The biological response was very complex; depending on the frequency of the fields, the effect can be stimulating or inhibitory.